Antimicrobial Therapy in Intensive Care Unit - Paramythiotou, Elizabeth; Routsi, Christina; Andremont, Antoine (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is an excellent collection of articles that deal with difficult-to-treat infections in the ICU environment. Multiresistant bacteria and fungi create severe treatment problems to the physician charged with their care. We hope that this book will help everyday dilemmas and add useful information on difficult topics.